The crisis of American business - James, Gene G. (Journal of business ethics, 1982)
This paper is a response to the preceding papers. It is maintained that American business is failing to live up to its obligations to society. One reason for this is acceptance of what De George calls the Myth of Amoral Business. Businessmen believe that morality is either not applicable to business or that business has a special morality of its own. Several arguments are advanced to show why this is not true. A second reason business is failing to fulfill its obligations is that egoism seems to be an essential feature of capitalism. Harrington believes that this should be changed, but that attempts to change it are bringing about a more collectivist society. Kirk sees no need for change because he believes capitalism the best possible economic system. It is argued in reply that they are both mistaken because their analyses are based on outmoded ideologies which impede rather than aid us in solving problems caused by the irresponsibility of business.